Exploration of computational thinking ability in limit concept of algebraic function with interactive multimedia - Lisa, Lisa; Pangaribuan, Lena Rosdiana; Panjaitan, Sorta Corie Ivana; Hasratuddin, Hasratuddin (SAINTIS Publishing, 2023)
The difficulty of students in solving computational thinking (CT) problems related to the limit material of algebraic functions is that students do not understand the existing problems, difficulties regarding how the problem-solving pattern, difficulties when asked how to solve the problem, and difficulties when deciding and concluding from the problem. To overcome these difficulties, interactive multimedia is used, which is very important in modern education, it allows students to learn in a more interesting and interactive way, which can strengthen students' computational thinking skills. The purpose of this study was to determine the Exploration of Computational Thinking ability in the concept of Limit algebraic function with interactive multimedia and to determine the student's response to the use of interactive multimedia on the computational thinking ability of students in the material limit algebraic function in the department of tadris mathematics IAIN Lhokseumawe. The method used in this research is pre-experimental method, with the research design used is One Group Pretest-Posttest (Initial Test-Final Test on a single group. The research subjects were 1st semester students majoring in Tadris Metematics IAIN Lhokseumawe academic year 2023/2024. The research results obtained 1) From the calculation of the t test obtained the results of Tcount amounting to 2.583 and Ttable 1.684 (Ttest Ttable) or the probability value Sig 2 tailed α (0.000 0.05), then the hypothesis decision can be stated Ho rejected and Ha accepted. Thus, there is a significant difference in the exploration of computational thinking ability in the concept of limit function algebra with interactive multimedia. 2) the average percentage of very good categories obtained a value of 86%, good 13%, less 1%. The difference from the results of student responses with good to very good criteria is influenced by attitudes that show enthusiastic positive responses to interactive multimedia.